Suicidal behaviour among those who attempted suicide and their close relatives/friends. (1st March 2011) - de Silva, P; de Silva, D; Jayasinghe, S; de Alwis Seneviratne, R; Abeyratne, M; Rajapakse, D; Mendis, N
Abstract : Objectives: To describe the repetition of suicidal attempts and the awareness of suicidal behaviour among close people. Methods: From 668 attempted suicides presented to National Hospital of Sri Lanka (April to December 2002), 300 were randomly selected and interviewed. Results: Previous suicidal attempts were present in 29 (9.7%) among which six have attempted more than twice. Majority (25, 86.2%) were deliberate self-poisoning (DSP) while few were intentional self harm (4, 13.8%). Knowledge of family or close friend who committed suicide was reported by 96 (32%). There were 13 (4.4%) reported suicides in biological family while 46 (15.4%) were close friends and 42 (14%) were neighbours. Among the known persons of DSP, drugs were consumed by 30 (43.5%) and pesticides by 26 (37.7%). Among intentional self harm the commonest method used was fire (11, 45.8%) and hanging/strangulation (07, 29.2%). The time lapse between the index suicidal attempt in the subjects was within 1 year of the suicidal attempt of the family member or friend in 45 (41.3%) of those who reported knowledge of a family member or close friend who committed suicide. Conclusion: The number with past suicidal attempts in our study is 10% which is a contrast to 54% reporting a previous suicide attempt in the WHO/EU multi-centre study on parasuicide. A total of 33% reporting knowledge of a close friend relative or neighbour who attempted suicide may indicate a strong influence of models in suicidal behaviour.